Innovation through PBL in the subject of history of advertising: The podcast as a learning tool - Rincón Alonso, Silvia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This project collects the work process carried out by 107 students in the subject of History of Advertising taught in the first year of the degree in Advertising at the Francisco de Vitoria University. This project has allowed the incorporation of Project-Based Learning as a teaching methodology and its application to the production of a podcast by students. In this sense, we see that both the PBL and the podcast are presented as an alternative to traditional learning methods, thus favoring the acquisition of the skills that are required of the student within the European Higher Education Area (EHEA).